(untitled) (Biological Sciences - PJSIR, 2019)
Aqueous and six solvent extracts of four seaweeds Codium tomentosum (Chlorophyceae); Corallina mediterranea, Hypnea musciformis (Rhodophyceae), and Sargassum vulgare (Phaeophyceae) were screened for their antibacterial activity against 10 gram-negative bacterial isolates. Seaweeds crude extracts potent antibacterial activity have been evaluated based on zone of inhibition (ZI), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values as reported in many researches. Overall, aqueous algal extracts were non active against all tested isolates regardless examined seaweed species. It was noticed that ZIs were in the following order: S. vulgare (17 mm) against Acinetobacter baumannii and C. mediteranea (17 mm) against Salmonella typhimurium > H. musciformis (13 mm) against Escherichia coli O:157 > C. tomentosum (11 mm) against S. typhimurium. Data revealed that the S. vulgare extracts showed the most inhibitory activity by showing the lowest MIC50 value of 0.08 mg/mL (methanolic extract against Shigella flexneri and hexane extract against E. coli O:157 isolate) and also the lowest MBC value of 1.00 mg/mL (methanolic extract against S. typhimurium, Serratia marcescens, E. coli O:157 and Brucella melitensis isolates; and also with ethanolic extract against S. marcescens and E. coli O:157 isolates). Future studies on the S. vulgare extracts are required due to their importance as a potent, promising and cheap source of bioactive compounds for antibacterial pretreatment.